Use of Continuous Electronic Fetal Monitoring in a Preterm Fetus: Clinical Dilemmas and Recommendations for Practice - Karolina Afors; Edwin Chandraharan (Journal of Pregnancy)
The aim of intrapartum continuous electronic fetal monitoring using a cardiotocograph (CTG) is to identify a fetus exposed to intrapartum hypoxic insults so that timely and appropriate action could be instituted to improve perinatal outcome. Features observed on a CTG trace reflect the functioning of somatic and autonomic nervous systems and the fetal response to hypoxic or mechanical insults during labour. Although, National Guidelines on electronic fetal monitoring exist for term fetuses, there is paucity of recommendations based on scientific evidence for monitoring preterm fetuses during labour. Lack of evidence-based recommendations may pose a clinical dilemma as preterm births account for nearly 8% (1 in 13) live births in England and Wales. 93% of these preterm births occur after 28 weeks, 6% between 22–27 weeks, and 1% before 22 weeks. Physiological control of fetal heart rate and the resultant features observed on the CTG trace differs in the preterm fetus as compared to a fetus at term making interpretation difficult. This review describes the features of normal fetal heart rate patterns at different gestations and the physiological responses of a preterm fetus compared to a fetus at term. We have proposed an algorithm “ACUTE” to aid management.